(untitled) (Journal of Plant Disease Sciences, 2021)
An in vitro experiment was conducted with the objective to find out the suitability of combination of agrochemicals (fungicides, insecticides and weedicides) with native bacterial antagonists like Pseudomonas fluorescens and Bacillus spp used in the integrative chickpea crop production. Twenty one agrochemicals were tested for their compatibility. Isolate P. fluorescence (CRSN-PF1) and Bacillus spp. (BRSN-B2) were found highly compatible with seed dressing chemicals (Thiophanate Methyl 45% + Pyraclostrobin 5% FS and Thiamethoxam 30% FS), fungicides (Thiophanate Methyl 70% WP and Copper Oxychloride 50% WP) and weedicides (2,4-D Amine Salt 58% SL, Oxyfluorfen 23.5% EC and Ammonium Salt of Glyphosate 71 % SG). For integrated pest management in chickpea, these agrochemicals along with the respective antagonists are recommended so as to reduce theenvironmental risk due to toxic pesticides and increase the sustainability of chickpea crop production.